Actualization of Al-Buthy's Jihad Concept in Modern Times - Madchaini, Kuntari; Rahimah, Rahimah (Fakultas Syariah Institut Agama Islam Negeri Lhokseumawe, 2024)
Nowadays, Islam is often considered as a radical teaching and embraced by extreme people, especially because of the teaching of jihad. So to straighten out this view, an in-depth study is needed that discusses the correct concept of jihad in Islam, and among the scholars who always try to do this is Al-Buthy. For this reason, the question of this research will answer how the concept of jihad according to Al-Buthy and how it is actualized in modern times. This research is qualitative research and uses normative juridical methods with a conceptual approach. The results of this study indicate that in the book al Jihad fi al Islam; Kaifa Nafhamuhu wa Kaifa Numarisuhu, Al-Buthy understands the meaning and nature of jihad as an oral da'wah to spread and uphold the sentence of Allah. The explanation is that every method or method carried out orally using any media is included in the act of jihad. This is the essence of jihad that was always carried out by the Prophet from the beginning of his mission as a Messenger until his death. Then regarding jihad in the sense of war, Al-Buthy interpreted the concept of Dar al-Islam. According to him, Dar al-Islam is an Islamic State, both those that were once under the Islamic caliphate and those that have now become fragmentary states. The concept of Dar al-Islam Al-Buthy is considered more realistic and contemporary. In contrast to the concept of Dar al-Islam promoted by some Muslim groups today, where they make the implementation of Islamic sharia in a kaffah as an absolute requirement of a country called Dar al-Islam. If not then the country is legitimately fought, the leader may be forcibly deposed, and even more extreme the country is considered a field of jihad war. So that the consequences of this concept are chaos and bloodshed as is happening now. For this reason, Al-Buthy emphasized the need to understand Islam by referring to the Islamic sciences inherited from the scholars, not from Islamic thought that developed following the times. Al-Buthy's method is considered moderate and more realistic to be actualized in modern times.